ENT600: Konsortium My Iqra Solutions (K-MiSs) / Zati Hanani Abu Talib … [et al.] - Abu Talib, Zati Hanani; Mohamad Dzaki, Nadirah; Mohamad Hassan, Farah Adibah; Sarom, Herwan (2019)
K-Miss is a local product which the idea was introduced by a group of friends. This company is growing up since they started to develop from 2011 until now, a lot of challenges and efforts has been done to stabilize this company so far. Various kind of joint ventures with extemal agencies influenced this company to be well known in Malaysia. Honey bee product is nutritious foods for all group of people who are really care about healthiness. The capital issue to start this business is not too much but the entrepreneurs will get a great profit after running this business.